Trehalose‐6‐phosphate synthase influences polysaccharide synthesis and cell wall components in Ganoderma lucidum. (6th July 2022) - Chen, Juhong; Fan, Junpei; Liu, Weidong; Wang, Zi; Ren, Ang; Shi, Liang
Abstract: Trehalose‐6‐phosphate synthase (TPS) is a key enzyme that participates in trehalose metabolism, which can synthesize trehalose in a two‐step pathway with trehalose phosphatase, but its role in fungi is rarely studied, especially in large basidiomycetes. In this study, the tps gene of Ganoderma lucidum was cloned and named as gltps . And gltps ‐silenced strains were constructed by RNA interference. In this study, it is found that the extracellular polysaccharide content increased 1.6–2‐fold, but there was no significant change on intracellular polysaccharide content in gltps ‐silenced strains compared with the wild‐type (WT) strain. Furthermore, the cell wall compositions of the gltps ‐silenced strains were also altered, which showed that the chitin and β‐1, 3‐glucan contents were significantly decreased. Compared with WT, the concentration of chitin decreased by 20%–50% and that of β‐1, 3‐glucan decreased by 15%–30%. The study found that the cells of gltps ‐silenced strains were more sensitive to cell wall stress, which might be due to changes in the compounds and structure of the cell wall. These results showed that gltps had an important effect on carbohydrate metabolism of G. lucidum cells.